Beauty in the age of empire Japan, Egypt, and the global history of aesthetic education - Adal, Raja (Columbia studies in international and global history., 2019)
"When modern primary schools were first founded in Japan and Egypt in the 1870s, they did not teach art. By the middle of the twentieth century, art education was a permanent part of Japanese and Egyptian primary schooling. Both countries taught music and drawing, and wartime Japan also taught calligraphy. Why did art education become a core feature of schooling in societies as distant as Japan and Egypt, and how is aesthetics entangled with nationalism, colonialism, and empire"--